The Influence of @tmghoteljakarta's Instagram Digital Marketing Content on Building Brand Awareness and Online Booking Decisions (Case Study: TMG Hotel Tebet, Marclan Collection, Jakarta) - Erika Munandari; Vidya Kusumawardani; Danang Trijayanto (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The purpose of this research is to analyze the influence of Instagram digital marketing content on brand awareness and its implications for online booking decisions at TMG Hotel Tebet. The research employs a quantitative approach using a survey method involving 158 hotel guests who have previously made an online booking and viewed the Instagram content of @tmghoteljakarta. Data were collected through a questionnaire using a five-point Likert scale as the research instrument. The data were analyzed using Partial Least Squares–based Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The results indicate that Instagram digital marketing content has a positive and significant effect on brand awareness, with a path coefficient of 0.522 (T-statistics = 9.152; p < 0.05). Furthermore, digital marketing content also has a positive and significant effect on online booking decisions. The coefficient of determination (R²) value of 0.272 shows that digital marketing and brand awareness explain 27.2% of the variance in online booking decisions. These findings confirm that optimizing informative, engaging, and consistent Instagram content can be an effective strategy to build brand awareness and simultaneously encourage online room booking conversions in the hospitality industry.